Process hazard considerations for utilization of renewable methane from biogas. Issue 4 (8th June 2022) - Dee, Sean J.; Hietala, David C.; Sulmonetti, Taylor P.
Abstract: Biogas production and use is a growing sector in the global alternative energy landscape. Biogas is a mixture of carbon dioxide and hydrocarbons (primarily methane) that is generated from the biological breakdown of organic material. This mixture can be separated and upgraded to produce renewable methane with a lower greenhouse gas footprint and cumulative energy demand than natural gas generated from fossil fuels. Biogas generation also typically provides an additional benefit of utilizing a waste stream as a feedstock. As industries and economies continue to produce organic waste, biogas and biomethane generation represent a large opportunity for production of sustainable fuels that can be used as drop‐in replacements for common fossil fuels. As a result, biogas generation and production of renewable methane are attractive technologies for industries with an aim to reduce their impact on the environment and meet sustainability goals. However, the production of biogas presents its own set of hazards and challenges that must be identified, analyzed, and mitigated. The paper will address common hazards (and how to manage the hazards) that a facility encounters when developing a project aimed at utilizing renewable methane through biogas generation.